STRATEGI INOVATIF UNTUK PEMBERDAYAAN MASYARAKAT DAN PENGEMBANGAN WILAYAH DENGAN REKOMENDASI PRAKTIS : STUDI KASUS - Amalia, Disa; Frinaldi, Aldri; Magriasti, Lince (Merwin Publisher, 2025)
Decentralization and local governance are important topics in the context of governance in Indonesia. Regional autonomy is the basis for giving authority to local governments in making decisions and managing resources at the regional level. Community empowerment and regional development are also the primary focus in achieving equitable and sustainable growth throughout Indonesia. This paper aims to describe the importance of decentralization in empowering communities and strengthening regional development in Indonesia. The research method used is a case study to analyze the implementation of decentralization and its effects on community participation and regional development. The research results show that decentralization has had a positive impact in empowering communities through active participation in local decision-making. In addition, sustainable regional development is also achieved through more effective allocation of resources and development programs based on local needs. However, there are still challenges that need to be addressed, such as regional disparities and a lack of local government capacity. Therefore, increasing the capacity of local governments, increasing community participation, and planning for sustainable development need to be the focus in efforts to optimize decentralization and strengthen local governance in Indonesia.